1974
DOI: 10.1128/aac.5.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Ethambutol Binding to Mycobacterium smegmatis

Abstract: Ethambutol uptake by Mycobacterium smegmatis and the relationship of uptake to growth inhibition have been under investigation in this laboratory (2,3). Kinetic experiments revealed a diphasic uptake pattern (2), in contrast to the apparent one-step reaction reported earlier by Forbes et al. (7). However, phase one uptake in our system had characteristics of the rapid binding described by the other workers, and growth inhibition depended on this primary interaction rather than on secondary uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…However, in contrast to EMB-treated M. smegmatis, there was no initial accumulation of lipids in this organism before their secretion. Beggs and Andrews showed that EMB binds almost instantaneously near the cell surface of M. smegmatis (2). Based upon these observations, it appears that the target site(s) for EMB is in the region of the cell surface.…”
Section: Discussionmentioning
confidence: 96%
“…However, in contrast to EMB-treated M. smegmatis, there was no initial accumulation of lipids in this organism before their secretion. Beggs and Andrews showed that EMB binds almost instantaneously near the cell surface of M. smegmatis (2). Based upon these observations, it appears that the target site(s) for EMB is in the region of the cell surface.…”
Section: Discussionmentioning
confidence: 96%
“…At selected time intervals, the cells contained in 8.0-ml samples were collected on bacteriological filter membranes (diameter, 2.54 cm; pore size, 0.8 j,m) under negative pressure. The cell-containing filter membranes were then washed three times with 2-ml volumes of either deionized water or drugfree Sauton medium, dried, and assayed for radioactivity as previously described (2). In the 37 C experiments, optical densities at 600 nm were determined at appropriate sampling times and converted to milligrams (dry weight) of cells per milliliter from a standard curve.…”
mentioning
confidence: 99%
“…Consequently, these species are regarded as being of minor significance in these titrations. With the exception of ethambutol protonation constants [28] no data for ethambutol or EDBA is available for comparison in the literature. However, neither exhibit any unexpected trends.…”
Section: Results and Dlseusslonmentioning
confidence: 97%